2014
DOI: 10.1186/1744-8069-10-4
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide is Neither Itch-Specific Nor Functions Upstream of the GRP-GRPR Signaling Pathway

Abstract: BackgroundA recent study by Mishra and Hoon identified B-type natriuretic peptide (BNP) as an important peptide for itch transmission and proposed that BNP activates spinal natriuretic peptide receptor-A (NPRA) expressing neurons, which release gastrin releasing peptide (GRP) to activate GRP receptor (GRPR) expressing neurons to relay itch information from the periphery to the brain (Science 340:968–971, 2013). A central premise for the validity of this novel pathway is the absence of GRP in the dorsal root ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 37 publications
10
63
1
Order By: Relevance
“…The thermal sensitivity of C2 correlates with the presence of Trpv1 and Trpv2 in the Nppb gene network and the role of NBP in thermal hyperalgesia [19,45]. Both C4 and C5 are MHNs (IS).…”
Section: Functional Annotations Of Neuron Types and Related Gene-netwmentioning
confidence: 99%
“…The thermal sensitivity of C2 correlates with the presence of Trpv1 and Trpv2 in the Nppb gene network and the role of NBP in thermal hyperalgesia [19,45]. Both C4 and C5 are MHNs (IS).…”
Section: Functional Annotations Of Neuron Types and Related Gene-netwmentioning
confidence: 99%
“…However, the number of neurons expressing Grp mRNA and GRP protein was consistently found to be ϳ8% and upregulated in DRG neurons, spinal primary afferents, and cutaneous nerve fibers in chronic itch conditions using IHC, ISH, or quantitative real-time PCR (Lagerström et al, 2010;Kagami et al, 2013;Nattkemper et al, 2013;Zhao et al, 2013;Liu et al, 2014;Takanami et al, 2014). Importantly, GRP immunostaining was completely lost in Grp KO mice Zhao et al, 2013), demonstrating that the anti-GRP antibody does not recognize other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…B-type natriuretic peptide (BNP) and its receptor natriuretic peptide receptor-A (NPRA) have been proposed to act upstream of GRP-GRPR signaling (Mishra and Hoon, 2013). However, other studies found that the BNP-NPRA pathway is important for nociceptive processing and is independent of the GRP-GRPR pathway (Zhang et al, 2010;Vilotti et al, 2013;Liu et al, 2014). GRPR (or BB2) is a member of the mammalian bombesin (Bn) receptor family, which comprises the following two other receptor subtypes: neuromedin B receptor [NMBR (or BB1)] and bombesin receptor subtype 3 (BRS-3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomic and pharmacological studies have demonstrated that GRP-GRPR system acts downstream of the BNP-NPRA signaling in the pruriceptive circuit as an itchselective regulation by BNP (Mishra and Hoon, 2013). However, a series of experiments conducted later indicated that BNP is neither itch-specific nor functions upstream of the GRP-GRPR signaling pathway (Liu et al, 2014). It is important to clarify the anatomic and pharmacological relationship between BNP-NPRA and GRP-GRPR systems in spinal regulation of itch.…”
Section: Introductionmentioning
confidence: 99%